Low-current Cathode with a BaO Based Thermoemitter. (2017) - Parakhin, G.A.; Pobbubniy, R.S.; Nesterenko, A.N.; Sinitsin, A.P.
Abstract: EDB Fakel has designed and operates a plasma cathode-compensator operating at Xenon flow rate of 0.15-0.20 mg/s at the discharge current of 1.25 A as a part of a 225 W powered SPT-50 stationary plasma thruster. After starting the thruster, the cathode requires no additional warm-up and its thermal mode is sustained by the discharge current. Such thrusters and cathodes are used on "Kanopus" spacecraft. When switching to high-voltage modes with a decreased discharge current the use of LaB6 as an emissive material poses difficulties, as the thermal power emitted on the thermoemitter is not sufficient for operation in a self-sustained mode. Emissive materials based on BaO, which are widely used abroad, are more suitable for discharge currents in the range of 0.4-1.0 A. Such material has been developed and tested as a part of a laboratory model. The results of the experimental test are presented below.